The altars of Republican Rome and Latium: sacrifice and the materiality of Roman religion - Moser, Claudia (Cambridge University Press, 2018)
The organization and boundaries of sacred places -- The economy of ritual: the site-specificity of votive offerings -- The seasonality of ritual: animal sacrifice -- Material memory